Behavioral and psychological consequences of social identity-based aggressive victimization in high school youth. Issue 1 (2nd January 2022) - Utley, Jessica Weiss; Sinclair, H. Colleen; Nelson, Sierra; Ellithorpe, Chelsea; Stubbs-Richardson, Megan
ABSTRACT: Research suggests many youth report being victimized in school due to ptheir social identities (e.g., race, gender, sexual orientation). We compared the consequences of social identity-based victimization (SIBV) to general victimization wherein adolescents are victimized by peers for other reasons (e.g., competition, a perceived insult). An online survey administered to 471 high school students yielded 777 victimization reports. 71.2% of the students reported at least one recent vicitimization, with 53.8% reporting SIBV. Race-based victimization was the most prevalent, and SIBV was more common online than offline. Psychological reactions (i.e., negative affect, self-esteem, and perceived costs) and behavioral responses (i.e., avoidant, antisocial, prosocial, and self-harm behavior), were heightened for youth reporting SIBV. As anticipated, psychological reactions significantly mediated the effect of SIBV on behavioral responses.